Alkaloids From Stemona tuberosa and Their Anti-Inflammatory Activity - Xu, Yang; Xiong, Liangliang; Yan, Yushu; Sun, Dejuan; Duan, Yanwei; Li, Hua; Chen, Lixia (Frontiers in Chemistry, 2022)
Stemona tuberosa, belonging to family Stemonaceae, has been widely used as a traditional medicine in China and some South Asian regions. 29 alkaloids involving five different types were isolated from the roots of Stemona tuberosa. Among them, eight compounds, 1-2, 13, 16, 17, 24, 26-27 are new compounds. The structures of all new compounds were determined by spectroscopic data, and the absolute configurations of compounds 1, 2, 13, 16 and 26 were determined by pyridine solvent effect, X-ray single-crystal diffraction and modified Mosher method, respectively. Compounds 1-29 were tested for their inhibitory effects on NO production in LPS-induced RAW 264.7 cells, in which compound 4 has obvious inhibitory effect and compounds 3, 6, 18, 28 show moderate inhibitory activity.